Health systems readiness and management of febrile outpatients under low malaria transmission in Vanuatu. (December 2015) - Zurovac, Dejan; Guintran, Jean-Olivier; Donald, Wesley; Naket, Esau; Malinga, Josephine; Taleo, George
Abstract Background Vanuatu, an archipelago country in Western Pacific harbouring lowPlasmodium falciparum andPlasmodium vivax malaria transmission, has been implementing a malaria case management policy, recommending parasitological testing of patients with fever and anti-malarial treatment for test-positive only patients. A health facility survey to evaluate the health systems readiness to implement the policy and the quality of outpatient management for patients with fever was undertaken. Methods A cross-sectional, cluster sample survey, using a range of quality-of-care methods, included all health centres and hospitals in Vanuatu. The main outcome measures were coverage of health facilities and health workers with commodities and support interventions, adherence to test and treatment recommendations, and factors influencing malaria testing. Results The survey was undertaken in 2014 during the low malaria season and included 41 health facilities, 67 health workers and 226 outpatient consultations for patients with fever. All facilities had capacity for parasitological diagnosis, 95.1 % stocked artemether-lumefantrine and 63.6 % primaquine. The coverage of health workers with support interventions ranged from 50 to 70 %. Health workers' knowledge was high only regarding treatment policy for uncomplicatedP. falciparum malaria (83.4 %). History taking and clinical examination practices were sub-optimal. Some 35.0 % (95 % CI 23.4–48.6) of patients with fever were tested for malaria, of which all results were negative and only one patient received anti-malarial treatment. Testing was significantly higher for patients age 5 years and older (OR = 2.33; 95 % CI 1.48–5.02), seen by less qualified health workers (OR = 2.73; 95 % CI 1.48–5.02), health workers who received malaria case management training (OR = 2.39; 95 % CI 1.28–4.47) and patients with increased temperature (OR = 2.56; 95 % CI 1.17–5.57), main complaint of fever (OR = 5.82; 95 % CI 1.26–26.87) and without runny nose (OR = 3.75; 95 % CI 1.36–10.34). Antibiotic use was very high (77.4 %) with sub-optimal dispensing and counselling practices. Conclusions Health facility and health worker readiness to implement policy is higher for falciparum than vivax malaria. Clinical and malaria testing practices are sub-optimal, however adherence to test negative results is nearly universal. Use of antibiotics is irrational. Quantitative and qualitative improvements of ongoing interventions are needed to re-inforce clinical practices in this area characterized by difficult access, human resource shortages but aspiring towards malaria elimination.